RP-HPLC METHOD DEVELOPMENT AND VALIDATION OF ASIATIC ACID ISOLATED FROM THE PLANT CENTELLA ASIATICA. - Hebbar, Srinivas; Dubey, Akhilesh; G. S., RAVI; Kumar, Hemanth; Saha, Santhanu (International Journal of Applied Pharmaceutics, 2019)
Objective: Asiatic acid is a triterpene saponin and the main constituent of the species Centellaasiatica. The current study aimed to isolate, characterize and develop an analytical method for asiatic acid in the shorter run time with good efficiency. Methods: In this study isolation of asiatic acid was achieved by TLC and thus isolated asiatic acid was characterized by 1HNMR spectral analysis and LCMS. An isocratic RP-HPLC method was established for the assessment of asiatic acid from the methanol extract of Centellaasiatica. The chromatographic separations were achieved by RP-C18 column 250x4.6 mm (5µ Particle size) Shimadzu UFLC pump LC 20AD and mobile phase composed of 0.1% orthophosphoric acid: acetonitrile (50:50). The analysis of column effluents was achieved using a PDA detector (Photo Diode Array) at 210 nm, and the flow rate was recorded 1 ml/min. Results: Soxhlet extraction process followed by fractional extraction using different solvents was performed. Methnol extract was taken to isolate asiatic acid by TLC (RF 0.97) and base peak from mass spectra was found to be 489M+which was confirmed successful isolation. Retention time of asiatic acid was found to be 9.6±0.22 min. This method obeyed linearity over the concentration range of 10-50µg/ml and regression coefficient was obtained from the alinearity plot for asiatic acid which was found to be 0.9987 LoD and LoQ were obtained to be 0.784507µg/ml and 2.615µg/ml respectively. RSD of mean assay values was found to be 1.02%. Since there were no marked changes in the performance characteristics of the method. Conclusion: Isolation, characterization and identification of asiatic acid were achieved significantly which will be useful for the standardization of herbal formulation containing asiatic acid.